Angular momentum evolution of bulge stars in disc galaxies in NIHAO. Issue 4 (10th November 2018) - Wang, Liang; Obreschkow, Danail; Lagos, Claudia del P; Sweet, Sarah M; Fisher, Deanne; Glazebrook, Karl; Macciò, Andrea V; Dutton, Aaron A; Kang, Xi
ABSTRACT: We study the origin of bulge stars and their angular momentum (AM) evolution in 10 spiral galaxies with baryonic masses above10^10 M_ in the Numerical Investigation of a Hundred Astrophysical Objects galaxy formation simulations. The simulated galaxies are in good agreement with observations of the relation between the specific AM and mass of the baryonic component and the stellar bulge-to-total ratio ( B / T ). We divide the star particles atz = 0 into disc and bulge components using a hybrid photometric/kinematic decomposition method that identifies all the central mass above an exponential disc profile as the 'bulge'. By tracking the bulge star particles back in time, we find that on average 95 per cent of the bulge stars formed in situ, 3 per cent formed ex situ in satellites of the same halo, and only 2 per cent formed ex situ in external galaxies. The evolution of the AM distribution of the bulge stars paints an interesting picture: The higher the final B / T, the more the specific AM remains preserved during the bulge formation. In all cases, bulge stars migrate significantly towards the central region, reducing their average galactocentric radius by roughly a factor 2, independently of the final B / T value. However, in the higher B / T (≳ 0.2) objects, the velocity of the bulge stars increases and the AM of the bulge is almost conserved, whereas at lower B / T values, the velocity of the bulge stars decreases and the AM of the bulge reduces. The correlation between the evolution of the AM and B / T suggests that bulge formation and disc formation are closely linked and cannot be treated as independent processes.